Health and Wellness Measurement Approaches for Mobile Healthcare - Khalili Moghaddam, Gita; Lowe, Christopher R. (SpringerBriefs in Computational Intelligence, 2019)
This book reviews existing sensor technologies that are now being coupled with computational intelligence for the remote monitoring of physical activity and ex vivo biosignatures. In today's frenetic world, consumers are becoming ever more demanding: they want to control every aspect of their lives and look for options specifically tailored to their individual needs. In many cases, suppliers are catering to these new demands; as a result, clothing, food, social media, fitness and banking services are all being democratised to the individual. Healthcare provision has finally caught up to this trend and is currently being rebooted to offer personalised solutions, while simultaneously creating a more effective, scalable and cost-effective system for all. The desire for personalisation, home monitoring and treatment, and provision of care in remote locations or in emerging and impoverished nations that lack a fixed infrastructure, is leading to the realisation that mobile technology might be the best candidate for achieving these goals. A combination of several technological, healthcare and financial factors are driving this trend to create a new healthcare model that stresses preventative 'health-care' rather than 'sick-care', and a shift from volume to value. Mobile healthcare (mhealth), which could also be termed the "internet of people", refers to the integration of sensors and smartphones to gather and interpret clinical data from patients in real-time. Most importantly, with an ageing population suffering multiple morbidities, mhealth could provide healthcare solutions to enhance chronically ill patients' quality of life.